PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN GOWA - Huda, Nurul; Rizal, Samsul; Rizaldi, Andi Risfan (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
This study aims to analyze the influence of motivation and job satisfaction on employee performance at the Department of Population and Civil Registration of Gowa Regency. Motivation and job satisfaction are crucial factors in enhancing employee productivity, which ultimately affects the effectiveness of public services. This research employs a quantitative method with a survey approach involving 65 employees as the sample. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The findings indicate that work motivation has a positive and significant effect on employee performance. Similarly, job satisfaction also has a positive and significant impact on employee performance. Therefore, increasing motivation and job satisfaction can enhance employee performance in providing administrative population services. These findings highlight the need for organizational strategies to improve employee welfare, create a conducive work environment, and provide appropriate rewards and incentives to boost employee motivation and job satisfaction.